Efektivitas Metode Discovery Learning Berbantuan E-Learning di SMA Negeri 1 Jepara - Sumianingrum, Ninok Eyiz (PEMBELAJAR: Jurnal Ilmu Pendidikan, Keguruan, dan Pembelajaran, 2017)
The research aims is to determine learning outcomes using the Discovery Learning methods in Edmodo Learning Management System, analyze the differences in learning outcomes of students using the Discovery Learning using Edmodo Learning Management with Discovery Learning aided by presentation applications, analyze the differences in learning outcomes of male and female students, and analyze the relationship between the Discovery Learning methods using Â Edmodo with the learning outcome of male and female students grade X SMAN 1 Jepara. Research conducted in a Quasi Experiment using a factorial design (2x2). Analysis of the data were used: (1) descriptive analysis to determine the average value of spiritual attitudes, social attitudes, projects, products, and response learners, and (2) inferential analysis using analysis Two Way ANOVA to test the hypothesis of treatment differences in learning outcomes of male and female student. The results showed that: (1) Discovery Learning methods using Edmodo contains six steps, (2) There are differences in learning outcomes of students who use the Discovery Learning methods by Edmodo with Discovery Learning aided by presentation applications (3) there are differences in learning outcomes of male andÂ  female students, and (4) there is no relationship between the method of Discovery learning aided application to the learning outcome of male and female students grade X SMAN 1 Jepara.Â